Excise Taxation of Sugar-Sweetened Beverages: A Legal Policy Approach to Public Health and State Budget Protection - Nugraha, Dwi Putra; Callista Yo, Beatrice; Cenniago, Sascha Kezia; Maurent, Vanessa (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2025)
The policy of imposing excise tax on Sugar-Sweetened Beverages is a strategic measure to reduce the growing incidence of Non-Communicable Diseases in Indonesia, particularly diabetes and obesity linked to the consumption of sugary drinks. The yearly increase in SSBs consumption harms public health and imposes a significant financial burden on the state, especially through the Social Health Security Administering Body (BPJS). Therefore, firm legal intervention is needed to limit consumption and promote a healthier lifestyle. The implementation of excise taxes on sugar-sweetened beverages should not be viewed merely as a fiscal instrument to boost revenue, but also as a means of protecting the public’s right to live a healthy and productive life. This policy must be understood as part of a broader public health strategy rather than solely an economic measure. Moreover, the policy is expected to encourage industries to reformulate their products into healthier alternatives to avoid excise taxation.